PENGARUH MODEL PEMBELAJARAN SEARCH, SOLVE CREATE, AND SHARE TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN MATEMATIKA KELAS V SDN 101775 SAMPALI - Tessalonika Ambarita; Elvi Mailani; Nurmayani; Natalia Silalahi; Syahrial (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT This study aims to determine the effect of the Search, Solve, Create, and Share (SSCS) learning model on students' critical thinking skills in Mathematics learning for fifth graders at SDN 101775 Sampali. This research was conducted at SDN 101775 Sampali using a Quasi-Experimental Design with a Nonequivalent Control Group Design. The subjects in this study were fifth grade students at SDN 101775 Sampali, consisting of two classes totaling 62 students. Data collection techniques were carried out through observation and tests. The instrument used in this study was an essay test to measure students' critical thinking skills. The results of the study showed a significant and positive influence between before and after the implementation of the SSCS learning model in improving critical thinking skills in fifth-grade mathematics learning. This is evidenced by the results of the hypothesis test with a t-test obtained a significance value of 0.045 <0.05. This indicates that H0 is rejected and Ha is accepted. Thus, it can be concluded that there is an influence of the Search, Solve, Create, and Share Learning Model on Students' Critical Thinking Skills in Fifth-grade Mathematics Learning at SDN 101775 Sampali.